2016
DOI: 10.1016/j.joca.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

MR T1ρ and T2 of meniscus after acute anterior cruciate ligament injuries

Abstract: Objective To evaluate differences in meniscal T1ρ and T2 quantification in patients with acute anterior cruciate ligament (ACL) injuries and to determine correlations of these differences with MR morphological grading and patient-reported outcomes. Design Bilateral knees of 52 patients with acute ACL injury and 20 healthy controls were scanned using 3T MRI T1ρ and T2 mapping in this prospective study. Quantitative analysis of the meniscus was performed in anterior and posterior horns of the lateral and media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…2). 15,38 Wang et al 38 reported significantly higher T 1 ρ and T 2 values in the meniscus, especially the posterior horn of the lateral meniscus, after ACL injury, which also correlated with worsening patient symptoms and knee function. In a longitudinal analysis of patients after ACL injuries, Knox et al 39 reported persistent abnormalities of the meniscus T 1 ρ and T 2 signal in the posterior horn of the medial meniscus.…”
Section: Meniscus Imagingmentioning
confidence: 97%
See 1 more Smart Citation
“…2). 15,38 Wang et al 38 reported significantly higher T 1 ρ and T 2 values in the meniscus, especially the posterior horn of the lateral meniscus, after ACL injury, which also correlated with worsening patient symptoms and knee function. In a longitudinal analysis of patients after ACL injuries, Knox et al 39 reported persistent abnormalities of the meniscus T 1 ρ and T 2 signal in the posterior horn of the medial meniscus.…”
Section: Meniscus Imagingmentioning
confidence: 97%
“…37 Given the similarities to articular cartilage, T 1 ρ and T 2 mapping allow for detailed evaluation of the meniscus. 38,39 T 2 * has been shown to be significantly longer in degenerative menisci relative to normal meniscal tissue. Intrasubstance degeneration of the meniscus may also be evaluated with dGEMRIC, given its ability to reflect the proteoglycan content of the tissue.…”
Section: Meniscus Imagingmentioning
confidence: 98%
“…In addition to cartilage, Wang et al also found elevation of T 1ρ and T 2 in the menisci of ACL-injured knees (Fig. 3) [59]. While these measurements themselves may not be considered Bfunctional^in the traditional biomechanical sense, this may provide an alternative to estimate joint laxity and the its proceding consequences.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…107 Recently, UTE T2* and T1ρ have been used to analyze deep zones of the cartilage where non-UTE imaging may not be sensitive enough. UTE T2* is able to measure deep layers of cartilage while T2 cannot.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%